Brief reflections on the rationality of the legislative process and its impact on the presumption and control of constitutionality of the criminal law (2017)
The relationship between rationality in the legislative process and the presumption of constitutionality of criminal law is considered in the present study. This, in accordance with the hypothesis that the smaller the rationality of the legislative proces